THE INFLUENCE OF CORPORATE GOVERNANCE ON FRAUDULENT FINANCIAL STATEMENTS: THE MEDIATING ROLE OF ISLAMIC SOCIAL RESPONSIBILITY DISCLOSURE - Olimsar, Fredy; Amir, Amri; Arum, Enggar Diah Puspa; Afrizal, Afrizal (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
This study aims to examine the effect of Corporate Governance on Fraudulent Financial Statements with the mediating role of Islamic Social Responsibility (ISR). The study was conducted using a sample of companies listed in the Jakarta Islamic Index (JII) 70, which includes company data for the period 2019–2022. The analysis method used in this study is Structural Equation Modeling (SEM) to test the relationship between variables. The results of the study indicate that Corporate Governance has a significant positive effect on Islamic Social Responsibility, indicating that companies with good governance are more likely to carry out sharia-based social programs and transparency in ISR reporting. Corporate Governance has a significant negative effect on Fraudulent Financial Statements, indicating that formal governance mechanisms such as the board of commissioners, board of directors and board committees are effective in suppressing the practice of financial statement manipulation. Islamic Social Responsibility has a significant negative effect on Fraudulent Financial Statements, which confirms that Islamic ethical values ​​implemented through ISR can reduce management incentives to commit fraud. Islamic Social Responsibility partially mediates the relationship between Corporate Governance and Fraudulent Financial Statements. The policy implications of this study are the need for synergy between strengthening formal corporate governance mechanisms and increasing Islamic social responsibility disclosures to create a transparent, accountable and ethical corporate culture. For regulators and practitioners in the sharia industry, especially JII70 companies, the results of this study can be used as a reference in designing more comprehensive governance and ISR guidelines.